An Intelligent Micro-service Chain Orchestrator for Immersive Media Services under the presence of Server Failure Events - Costa, Erick; Flexa, Rodrigo; Brito, Matheus; Santos, Hugo; Astudillo, Carlos; Rosário, Denis; Cerqueira, Eduardo (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS); 2025: Anais do XXX Workshop de Gerência e Operação de Redes e ServiçosDO - 10.5753/wgrs.2025.8773, 2025)
Immersive Multimedia Services (IMS)s combined with advanced communication technologies, such as beyond 5G (B5G) and 6G, has advanced constraints for low latency and high throughput, offering a fluid and improved user experience. This is achieved by the use of Multi-access Edge Computing (MEC) infrastructure to distribute resource consumption for decentralized service execution between the head-mounted glasses and the central network node. In this context, Micro-service Chain (MSC) orchestration algorithms offer an efficient distribution of resource consumption in the available MEC infrastructure, avoiding interruption in experience and increasing quality. However, it is required robust orchestration strategies for service recovery in cases of connection node failure. This paper introduces an Intelligent MSC Orchestration algorithm for IMS applications under the presence of MEC server failures, called IMSCO. The algorithm uses Genetic Algorithm to determine the optimal routing paths between clients and parallelizable, ordered, and location-aware MSs instantiated at MEC servers, considering computational and network constraints, latency, and client mobility. The comparative results highlight a recovery success 90% in fail events with 5% acceptance ratio improvement to literature algorithms, showcasing advancements ensuring resilient and high-quality immersive service delivery.